Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1002/fld.2066
|View full text |Cite
|
Sign up to set email alerts
|

An approximate‐state Riemann solver for the two‐dimensional shallow water equations with porosity

Abstract: SUMMARYPorAS, a new approximate-state Riemann solver, is proposed for hyperbolic systems of conservation laws with source terms and porosity. The use of porosity enables a simple representation of urban floodplains by taking into account the global reduction in the exchange sections and storage. The introduction of the porosity coefficient induces modified expressions for the fluxes and source terms in the continuity and momentum equations. The solution is considered to be made of rarefaction waves and is dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 34 publications
0
33
0
Order By: Relevance
“…For shallow ows over natural topographies, the porosity is depth-dependent [1,5,6,39], while urban ood applications consider a depth-independent porosity [15,16,37,38]. A number of numerical solution techniques have been developed for the depthindependent SP equations [2,4,8,15,26]. Recently, a generalized source term has been proposed for the specic purposes of urban ood modelling [38].…”
Section: Introductionmentioning
confidence: 99%
“…For shallow ows over natural topographies, the porosity is depth-dependent [1,5,6,39], while urban ood applications consider a depth-independent porosity [15,16,37,38]. A number of numerical solution techniques have been developed for the depthindependent SP equations [2,4,8,15,26]. Recently, a generalized source term has been proposed for the specic purposes of urban ood modelling [38].…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to tackle the issue in a more theoretical way have also been made by many other researchers, e.g. Rogers et al 26, Lhomme andGuinot 27, Liang and Borthwick 28, Lee and Wright 29 and Finaud‐Guyot et al 30. Nonetheless, this review is far from complete due to the extensive research involved in this topic (useful reviews may be found in 2, 31, 32).…”
Section: Introductionmentioning
confidence: 96%
“…Once the matrices R(U) and R −1 (U) are calculated the sign matrix can be easily updated according to (9).…”
Section: Determination Of the Sign Matrixmentioning
confidence: 99%
“…Similar free-surface flow models have been developed in [10,19] and the references therein. Applications of shallow water flows with porosity have also been studied in [7,9,11,13,14,22,23] among others. The governing equations form a two-dimensional nonlinear system of hyperbolic conservation laws with source terms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation